Going back to Kahlbaum’s psychomotor (and GABAergic) origins: is Catatonia more than just a motor and dopaminergic syndrome? - Hirjak, Dusan; Kubera, Katharina Maria; Wolf, Robert Christian; Northoff, Georg (Schizophrenia bulletin, 2019)
Abstract. In 1874, Karl Kahlbaum described catatonia as an independent syndrome characterized by motor, affective, and behavioral anomalies. In the following ye